Psychiatric morbidity among the patients of first ever ischemic stroke (Bangladesh Journal of Psychiatry, 2022)
Ischemic stroke is one of the leading causes of mortality and morbidity worldwide and third common cause of death in developed countries which consumes annually a great cost, directly or indirectly and stroke produces a wide range of psychiatric disorders. This was a cross sectional study, conducted in the department of Psychiatry, Sylhet MAG Osmani Medical College Hospital, Sylhet during the period from 1 July 2013 to 30 June 2014 to evaluate the psychiatric morbidity among the patients of first ever ischemic stroke. For this purpose, 66 ischemic stroke patients of first attack between 2 weeks to 2 years of stroke, aged above 18 years irrespective of sex and 66 accompanying healthy persons of the patients and other patients without any kind of stroke matching age and sex fulfilling inclusion and exclusion criteria were taken in Group[1]A and Group-B respectively. Psychiatric assessment was done using General Health Questionnaire (GHQ12) as a screening tool and all GHQ12 positive cases were evaluated using mental state examination. Diagnoses of psychiatric disorders of all respondents were confirmed by psychiatrist according to Diagnostic and statistical manual of mental disorders (DSM) 5 criteria. Ethical issues were maintained properly and an informed written consent was taken from every patient. After collecting data, editing was done manually and was analyzed with statistical package for social sciences (SPSS) version 21. The result showed that, the mean age of the respondents was 57.6 (SD±5.5) years which was almost identical to control group (p=0.130). Most (87.9%) of the patient were below the age of 65 years. Co-morbid psychiatric disorder was found in (34.8%) patients with ischemic stroke and (13.6%) control subjects (p=0.004). The most common psychiatric disorder was generalized anxiety disorder (13.6%) and major depressive disorder (21.2%) in ischemic stroke group. The results of this study suggested that, a significant number of patients with ischemic stroke were suffering from psychiatric disorders than the age and sex matched control.   Bang J Psychiatry 2022;36(1):11-17